Efeito da Fotobiomodulação Laser em Pacientes com Desordem Temporomandibular - Lira, Eloysa Marques de (Brasil, 2024)
Temporomandibular disorder (TMD) is a multifactorial condition, that is, it has several causes that can influence the patient's clinical condition. The main causes include stress, bruxism, anxiety, postural changes, trauma and genetic changes. TMD can cause harm to an individual's daily life, such as speaking, chewing, yawning and even changes in sleep, contributing negatively to the reduction of patients' functional capacity and quality of life. In this study, we sought to verify the effect of Low Intensity Laser Therapy on patients with Temporomandibular Disorder in the city of Coari-AM, in the interior of Amazonas. This is a double-blind randomized clinical trial, with 15 participants, the study was divided into three (3) groups: control, placebo, LTBI. The allocation of participants to the respective groups was carried out randomly. In the control group, no type of intervention was carried out, but there were (10) ten days of follow-up. In the LTBI and Placebo group, (1) were performed once a day, from Monday to Friday, Saturday and Sunday intervals. The sample for this study was made up of 15 participants of both sexes, with pain lasting more than 3 months. The group studied presented the following characteristics, mean age of 38.66±18.78. Participants involved in the study were treated for 12 sessions. It can be concluded that low-intensity laser FBM, in the parameters used in this study, was effective for the treatment of TMD, reducing pain intensity and increasing the range of motion of the TMJ, providing a better quality of life for patients. Keywords: Temporomandibular joint; Photobiomodulation; Pain; Range of motion